Penerapan Algoritma Elias Gamma Code Pada Aplikasi Kumpulan Resep Makanan Berbasis Android - Siregar, Roslina (TIN: Terapan Informatika Nusantara, 2021)
The size of the text file is sometimes relatively large where the better the quality of the resulting text file, the file size needed to store the text file is getting bigger. With a very large text file size, at the time of the transfer process, the transfer process might fail because the storage space exceeds the limit. Compression in text files is done by reducing the size of the text file by reducing the bit in the text file. By doing large data compression will reduce its size so that it can save storage space. The results used to implement the Gamma code elias algorithm by using the algorithm results of compression of values ​​have different results from each value, and the results of compression will be advantageous in sending and transferring text files will be easier